ANALISIS NILAI- NILAI KARAKTER YANG TERKANDUNG PADA BUKU MATA PELAJARAN PENJASORKES KURIKULUM 2013 KELAS IV SEKOLAH DASAR - Ikhsan Maulana Putra; Sharifa Nigrum (Jurnal Muara Pendidikan, 2021)
Character is a personality that includes several broad aspects, be it the quality or mental strength of a person, it is also included in morals or morals and this is the special personality of the individual. Character education is a continuous education, character education can be obtained from an early age provided by the family environment to formal education, namely from kindergarten to college, character education must create an integrated character values ​​contained therein. The research objective in this study was to describe the forms of character values ​​contained in the student books for the subject of physical education in the curriculum 2013 class IV Elementary School 88 / II Sungai Mengkuang. This study used a qualitative descriptive type of research which provided an overview, presented directly the nature of the relationship between the researcher and the informant, and analyzed the character values ​​contained in the students' books of physical education for the fourth grade of elementary school physical education. The results of the research in the discussion that have been described above can be concluded that there are many character values ​​in the subject matter in the fourth grade physical education book but still not in accordance with the implementation of the 2013 curriculum where there are still values ​​that have not been applied. The results of research in the discussion that have been described above can be concluded that there are many character values ​​in the subject matter in the fourth grade physical education book but still not in accordance with the implementation of the 2013 curriculum where there are still values ​​that have not been applied, and from Some of the subject matter above the character values ​​in this material only applies some social values, there are still social values ​​that have not been applied.